Unmasking the 'New Normal' and the 'Vernacular of the Veracious' during a Pandemic - Agcaoili, Aurelio S. (Budhi: a Journal of Ideas and Culture, 2021)
This paper argues that the deployment of a figurative language like the phrase "new normal" and many other verbal formulations during a pandemic is a form of power and control by political leaders. This deployment is calculated and calculating as it is meant to condition the minds of the masses that depend on the ruling political class for clarity, guidance, and some form of redemption. These "weaponized" words are presented as expression of veracious - essentially a vernacular of power - by persons of authority for a semblance of credibility. There are at least two versions of the veracious that are at play in the communities of infected people: (a) the official sense of what is true and (b) the hidden, unacknowledged "state of affairs" that is known only by the ruling power. The unevenness of communication during the pandemic gives the state full control of the calculated and calculating message, leaving the recipients of the official message reduced to helpless consumers. In these Covidized days of our lives, there is nothing normal in the "new normal." It is an abnormality. Likewise, the "vernacular of the veracious" is plain propaganda for the wrong reason and needs to be turned into a "new paradigm."